THE ROLE OF ELECTRONIC WORD OF MOUTH IN MODERATING THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER LOYALTY (A STUDY AT EL LAGO BALI) - Hooky Surya Widarma; Ni Made Purnami (Adisam Publisher, 2025)
Customer loyalty refers to a consumer's commitment to continue repurchasing the same product or service as a result of positive experiences or favorable impressions of the product or service. It reflects a consumer's tendency to repeatedly purchase preferred products or services. This study aims to examine and explain the effect of service quality on customer loyalty, as well as the moderating role of electronic word of mouth (e-WOM) in the relationship between service quality and customer loyalty at El Lago Bali. The sample consists of 100 respondents selected using purposive sampling. Data were collected through questionnaires, and the data analysis technique employed was Moderated Regression Analysis (MRA). The findings reveal that service quality has a positive and significant effect on customer loyalty, and electronic word of mouth effectively moderates the influence of service quality on customer loyalty.